Earsplitters! the world's loudest noises - Parker, Steve, 1952-; Polly Goodman : Shelley Noronha (Mankato, Minn. : Capstone Press, 2009)
"Presents the science behind sound including dragster races, rock concerts, and rockets"--Provided by publisher.
Includes index.
Includes bibliographical references and index.
Keywords: Noise -- Juvenile literature; Sounds -- Juvenile literature